ANALISIS PENGARUH LIKUIDITAS, LEVERAGE, AKTIVITAS, PROFITABILITAS, DAN GROWTH TERHADAP KEBIJAKAN DIVIDEN EMITEN YANG TERDAFTAR PADA INDEKS LQ-45 PERIODE 2011-2013 - Sulaiman, Hengky; Sumani, Sumani (Jurnal Manajemen, 2016)
Dividend is component of return that investor gain on stock investment. On other side, dividend policy ismajor cash outlay for the company. The research goal is to reveal the factor that significantly influence thedividend policy, which can be used to maximize the investor’s return and provides guidance for thecompany in determining dividend policy.The research used sixteen company listed on LQ-45 Indexes during 2011-2013 by using panel dataanalysis. The research shows that activity and growth significantly affect the dividend policy whileliquidity, leverage, and profitability insignificantly affect the dividend policy.